Media Sosial Dalam Propaganda Terorisme Perspektif Fikih Siyasah - Muhajir, Ahmad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Social media has become the primary platform for terrorist groups to disseminate propaganda and recruit new members. This study aims to analyze the impact of social media usage in terrorism propaganda from the perspective of Islamic jurisprudence (fiqh). Through a fiqh-based approach, this research identifies the principles underlying Islamic law concerning the use of social media in spreading terrorist messages. The research methodology involves analyzing relevant fiqh texts and studying literature on the role of social media in the dissemination of radical ideologies. The findings highlight the importance of involvement of religious scholars and leaders in deconstructing the narratives of terrorism disseminated through social media. Additionally, the research emphasizes the need for a holistic approach that encompasses legal, social, and technical aspects to address the influence of social media in terrorism propagation. The findings highlight the importance of involvement of religious scholars and leaders in deconstructing the narratives of terrorism disseminated through social media. Additionally, the research emphasizes the need for a holistic approach that encompasses legal, social, and technical aspects to address the influence of social media in terrorism propagation. The implications of this research underscore the importance of developing prevention strategies based on a deep understanding of fiqh to counter the spread of terrorism propaganda through social media.